Synthesis, characterization and in vitro study of magnetic biphasic calcium sulfate-bioactive glass - Goh, Yi-Fan (2015)
Calcium sulfate-bioactive glass (CSBG) composites doped with 5, 10 and 20 mol% Fe were synthesized using quick alkali sol-gel method. X-ray diffraction (XRD) data of samples heated at 700°C revealed the presence of anhydrite, while field emission scanning electron microscopy (FESEM) and energy dispersive X-ray (EDX) characterization confirmed the formation of nano-sized CSBGs. The UV-vis studies confirmed that the main iron species in 5% Fe and 10% Fe doped CSBGs were tetrahedral Fe(III) whereas that in 20% Fe doped CSBG were extra-framework FeOx oligomers or iron oxide phases. Measurement of magnetic properties of the samples by vibrating sample magnetometer (VSM) showed very narrow hysteresis loop with zero coercivity and remanence for 10% Fe and 20% Fe doped CSBG, indicating that they are superparamagnetic in nature. All samples induced the formation of apatite layer with Ca/P ratio close to the stoichiometric HA in simulated body fluid (SBF) assessment.